SISTEM AKUNTANSI SUMBER DAYA MANUSIA UNTUK KINERJA PERUSAHAAN - -, Suprayitno - (Universitas Slamet Riyadi, 2004)
ABSTRACT Â Accounting system for business organization is widely known by economic society, especially for those who are interest in accounting. On the other hand human resource accounting system in accounting, hasnâ€™t been know widely. Human resource accounting system which is usually used by business organizational, both service and industrial organization, is conventional accounting. This system treats all expenses concerned with human resources as one expense, consequently this expense will be deleted directly is related period. The review of human resources accounting system need to be done basically, moreover it must be based on human resource treatment properly. Human resource has no longer the same position and treatment with other resources. Keywords: accounting system, human resource management, organization performance